Development of socioeconomic indicators for measuring the population wellbeing in lembah klang-langat extended metropolitan region, malaysia. Issue 1 (March 2021) - Saleh, Y; Mahat, H; Hashim, M; Nayan, N; Norkhaidi, S B; Mohd Zanuddin, I H
Abstract: This paper aims to develop a socioeconomic indicators to measure the wellbeing of the people in Lembah Klang-Langat Extended Metropolitan Region (EMR). A total of 400 respondents comprised heads of household in 15 settlement centres in Lembah Klang-Langat Extended Metropolitan Region (EMR) were selected as study sample. Quantitative approaches using SPSS and AMOS software were in this study. The data were analysed using factor analysis, namely exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The results showed that after EFA and CFA had been applied, only two sub-constructs of socioeconomic construct which were i) social, and ii) economy, and six items of B7_3, B7_4, B7_5, B7_7, B7_10 and B7_11 presented high validity values of CR exceeding 0.6. The analysis found that the measurement model met the measurement criteria for measuring suburban wellbeing. The study findings also showed that the similarity index value was equal to p=0.000, chi-square relative value of 3.553, 0.991 for GFI value, 0.983 for CFI value, 0.968 for TLI and RMSEA value of 0.051. Therefore, the findings of this study have successfully prepared a set of socioeconomic indicators that can be used by future researchers for analysing the wellbeing of socioeconomic aspect of metropolitan region's extended area.